INSTAGRAM AS A DA'WAH MEDIA (ANALYSIS OF THE CONTENTS OF NING SHAILA HASINA'S DA'WAH MESSAGES) - Firdausiyah, Rofiqotul Afifah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The availability of several social media facilities that are very popular with teenagers unknowingly becomes a threat and damage if it is not accompanied by self- and emotional control as well as directions and advice from other people who have qualified knowledge. However, in this millennial era it is very difficult to gather teenagers in an Islamic study or da'wa. For this reason, it is important for the accusers to enter the modern, millennial world and use social media such as Instagram, Tik Tok, Twitter and so on.This study aims to examine the "InstagramAs a Da'wah Media (Analysis of the content of Ning Shaila Hasinah's Da'wah Message)”, using qualitative research methodology with the type of literature study (Library Research) which uses several books, journals, and other literature as the main object to obtain data regardingInstagram as a medium of da'wah. Based on the results of these studies arethe da'wah messages shared by Ning Shaila Hasina with the Instagram account @sheilahasina in the highlights on her Instagram account share her da'wah content with several messages, ranging from messages and advice for women, especially in understanding the chapter on menstruation and childbirth, and how to have educated children Of course, it must be handled by an educated mother. Da'wa's messages are related to several Islamic lessons and motivations, Dakwah's messages are related to matters in obtaining enormous worship value through understanding the special deeds of Ashurul Hurum or the month that Allah glorifies.